2017
DOI: 10.1097/md.0000000000008919
|View full text |Cite
|
Sign up to set email alerts
|

The safety of concomitant transcatheter aortic valve replacement and percutaneous coronary intervention

Abstract: Background:TAVR is a rapidly spreading treatment option for severe aortic valve stenosis. Significant coronary artery disease (CAD) is present in 40% to 75% of patients undergoing TAVR. However, when to treat the concomitant coronary artery lesions is controversial.Methods:This is a systematic review comparing concomitant PCI and TAVR versus staged PCI and TAVR. The OVID database was systematically searched for studies reporting PCI in patients undergoing TAVR. A random effects model was used to calculate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Some recent meta‐analysis of observational studies revealed no difference in short‐term safety outcomes using either staged PCI and TAVR or synchronous PCI and TAVR procedure, however, as the authors mentioned, the results are subject to various confounding factors 26 …”
Section: Discussionmentioning
confidence: 96%
“…Some recent meta‐analysis of observational studies revealed no difference in short‐term safety outcomes using either staged PCI and TAVR or synchronous PCI and TAVR procedure, however, as the authors mentioned, the results are subject to various confounding factors 26 …”
Section: Discussionmentioning
confidence: 96%
“…A recent meta-analysis, based on observational data comparing the short-term safety outcomes of concomitant versus staged PCI with TAVI in severe AS patients, demonstrated that the 30-day all-cause mortality and other major safety endpoints did not significantly differ between the two approaches [ 113 ]. Notably, the pooled rate of renal failure was not statistically different between the two groups, although the incidence was relatively higher in the concomitant PCI and TAVI group (5% versus 2.2%) [ 113 ]. Another disadvantage of combining two procedure in the same session is the increased of the procedural complexity as well as the operator fatigue.…”
Section: Timing Of Percutaneous Coronary Interventionmentioning
confidence: 99%
“…Simultaneous procedures have the advantage of decreasing repeated puncture or incision of vessels, reducing patients' suffering and length of hospital stay, and saving medical resources [11] . However, radiation exposure and the amount of contrast used are usually higher [12] .…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%
“…PCI before TAVI, on the other hand, has the potential to minimize ischemic risk during TAVI, particularly during rapid ventricular pacing, and to overcome difficulties associated with coronary access post-TAVI. Conversely, the patient remains at risk for valvular decompensation and needs to be put on dual antiplatelet therapy, which may increase the risk of bleeding during TAVI [11][12][13] . PCI after TAVI is relatively rare because prosthetic valve commissures, or stent frame, may be positioned close to coronary ostia, interfering with coronary diagnostic or guiding catheters [14] .…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%
See 1 more Smart Citation